Implementasi Low Power Pada Embedded System Untuk Mendeteksi Kondisi Kebakaran Dalam Ruangan - Rinaldi Albert Soritua; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Fire is an event caused by unrestrained fire by human. Fire could cause various losses from treasures to casualties. Based from that problem needed a system that able to detect fire based on smoke level, room temperature, dan existence fire source. In implementation needed low power to save power consumption when system not detect a fire. The output of the system is current condition which is no fire, fire and smoky little, fire smoky and lot that shown on LCD and sound from buzzer. Arduino Mega 2560 implanted fuzzy logic as output decision based on fuzzy calculation. If system not detect a fire then system will switch to sleep mode, yet if system detect an output which is smoky, fire and smoky little, fire smoky lot it will shown on LCD and sound from buzzer. The used feature is sleep mode power down to turn off some sub-system. Testing resulted system is running accordance with the principles of it works. The average system execution is Â±33284,2 ms. On the power consumption of the device is able pressed for 40mA from 245mA to 205mA with implementation sleep mode power down.